IMPLEMENTASI BLENDED LEARNING DI MATA KULIAH APLIKASI SIG PADA PENDIDIKAN GEOGRAFI UNP - Azizah, Shofiyah Fia; khairani, Khairani (JURNAL BUANA, 2023)
This study aims to explore the blended learning learning model in the GIS application course for geography education students 2020 which includes the processes and inhibiting factors. This type of research is a mixed research method that combines quantitative and qualitative research methods and uses a quantitative approach with descriptive methods. Data was collected by means of observation, questionnaires/questionnaires, interviews and documentation. Sampling using simple random sampling technique to 20 students from 93 students. Based on the results of the study, it was concluded that the Implementation of the Blended Learning Learning Model in the GIS Application Course at the UNP Geography Education Study Program could be implemented well for the 2020 geography education students because the results of the questionnaire showed an average of 65%. Meanwhile, the inhibiting factor of blended learning is that students often experience problems on laptops that cannot be used to practice on mapping applications and do not understand the application of data in ArcGIS and have difficulty carrying out learning practicums.